2007
DOI: 10.1515/bmt.2007.011
|View full text |Cite
|
Sign up to set email alerts
|

Fetal ECG extraction during labor using an adaptive maternal beat subtraction technique

Abstract: Fetal ECG (FECG) monitoring using abdominal maternal signals is a non-invasive technique that allows early detection of changes in fetal wellbeing. Several other signal components have stronger energy than the FECG, the most important being maternal ECG (MECG) and, especially during labor, uterine EMG. This study proposes a new method to subtract MECG after detecting and removing abdominal signal segments with high-amplitude variations due to uterine contractions. The method removes MECG from abdominal signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…The main problem of its practical implementation is the interfering maternal electrocardiogram (MECG), many times exceeding the signal of interest. A number of different approaches for the suppression of the MECG and the detection of fetal QRS complexes have been presented in the literature [18,34,36] ; however, thus far, there has been no comprehensive study evaluating the accuracy of FHR measurement in abdominal FECG signal, on a beat-to-beat basis. It should be mentioned that accuracy is a crucial issue in the interpretation of the FECG, as it directly affects the variability assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem of its practical implementation is the interfering maternal electrocardiogram (MECG), many times exceeding the signal of interest. A number of different approaches for the suppression of the MECG and the detection of fetal QRS complexes have been presented in the literature [18,34,36] ; however, thus far, there has been no comprehensive study evaluating the accuracy of FHR measurement in abdominal FECG signal, on a beat-to-beat basis. It should be mentioned that accuracy is a crucial issue in the interpretation of the FECG, as it directly affects the variability assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, three major classes have been identified, namely the ICA, 31 template subtraction, 20,36,40 and adaptive filtering, 37, 38 even though several others have been proposed in the literature. 42,43 The suitability of ICA technique for fECG extraction is not obvious considering that the purely mathematical basis of the method does not consider the several characteristics of the involved physiological signals.…”
Section: Discussionmentioning
confidence: 99%
“…36 More rarely, the template is computed from all segmented beats using particular adaptive filters. 40 Once the template has been constructed, all maternal beats are reconstructed and concatenated to estimate amECG, which is eventually subtracted from faLead. 36…”
Section: Template Subtractionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, fewer algorithms depend on the singlelead aECG signal; e.g., template subtraction (TS) [13,[23][24][25][26], and its variation based on singular value decomposition (SVD) or principal component analysis [27,28], the time-frequency analysis, like wavelet transform, pseudo-smooth Wigner-Ville distribution [29][30][31][32] (in practice, three aECG channels are averaged in [30]), and S-transform [33], sequential total variation [34], adaptive neuro-fuzzy inference system and extended Kalman filter [35], particle swarm optimization and extended Kalman smoother [36] state space reconstruction via lag map [37,38], etc. We refer the reader to, e.g., Sameni and Clifford [4] and Andreotti et al [39] for a more detailed review.…”
Section: Introductionmentioning
confidence: 99%